The effect of unemployment and post-natal care on the exclusive breast-feeding practice of women in Ethiopia: a systematic review and meta-analysis - Mekdes Hailegebreal Habte; Seada Jemal Seid; Ayinalem Alemu; Hanna Abera Hailemariam; Birhanu Asrat Wudneh; Rahel Nega Kasa; Zebenay Workneh Bitew (Reproductive Health, 2022)
Plain Language summary Promotion of EBF in developing countries including Ethiopia is very crucial strategy to improve the survival of children. Despite this, several factors prohibit women from practicing EBF of which post-natal care service utilization and employment status are the main determinants. The previous studies in Ethiopia are inconsistent and inconclusive to policy makers. Thus, this systematic review and meta-analysis underpinned the effects post-natal care service and maternal employment status on the EBF practice of women in Ethiopia. The findings of this study will be vital to forward recommendations on the duration of maternal leave and design promotion strategies of post-natal care, the most unaddressed maternal health care service in Ethiopia. The original studies were retrieved systematically from reputable databases and grey literature sources. The data were extracted using standardized data extraction sheet. Analyses were performed using STATA software. Fixed and random effect models were utilized to compute pooled estimates. Heterogeneities were computed and the sources of heterogeneities were explained. In the current study, the pooled prevalence of EBF was 62.6%. Likewise, post-natal care service utilization and employment status were found to have significant association with the EBF practice. Unemployed women had a better EBF practice as compared to the employed ones. This could be due to the fact that most employed women in Ethiopia are governmental employees where the maximum duration of maternal leave is four months after birth. This is before the due date of commencement of complementary feeding. Post-natal care should also be promoted to improve the EBF practice.